Investigation of machinability properties of aluminium matrix hybrid composites - Turgut, Yakup; Okay, Faik; Islak, Serkan (Elsevier BV, 2021)
Abstract In this study, machinability properties of aluminium matrix boron carbide (B4C) and carbon nanofiber (CNF) reinforced hybrid composite material produced by powder metallurgy in drilling were investigated. In the study, the samples produced with hot pressing technique having 6 different volume rates were used. The drilling operations were performed using drills with 3 point angles (90°–118°–135°) at 30–45-67.5 m/min cutting speed and 0.1–0.15–0.225 mm/rev feed rate. As a result of the experiments, the thrust force, moment, and surface roughness were measured and the delamination factor forming at hole exits was calculated. In addition, the effect of reinforcement rate on the machinability was also investigated. In all drill types, it was determined that as the feed rate increased, the thrust force increased and as the reinforcement rate increased, moment values also increased. Surface roughness values increased with the increased feed rate but decreased as the cutting speed increased. As the drill point angle increased, the surface roughness value decreased but the hole exit damage increased.